2008
DOI: 10.1111/j.1349-7006.2008.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and colorectal adenomas: Self Defense Forces Health Study

Abstract: Adiponectin is an adipocyte-derived protein with an insulinsensitizing action. Circulating levels of adiponectin are inversely correlated with obesity, especially abdominal obesity. Some studies have suggested that low levels of circulating adiponectin might be related to increased risk of colorectal cancer and adenomas. The present study examined the relationship between total and highmolecular-weight (HMW) adiponectin to colorectal adenomas in the Self Defense Forces (SDF) Health Study. The study subjects co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
1
27
0
4
Order By: Relevance
“…Although the function of most SNPs remains unclear, it has been shown that two common SNPs, rs1501299 (G276T) and rs2241766 (T45G), may affect disease susceptibility. They have been associated with serum adiponectin (20)(21)(22)(23)(24)(25)(26), obesity (21,25,27,28), insulin sensitivity (18,21,29), type II diabetes (17,20,30) and coronary artery disease (24,31). However, some of these associations have been unable to be confirmed in other studies and the results have been controversial (32)(33)(34).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Although the function of most SNPs remains unclear, it has been shown that two common SNPs, rs1501299 (G276T) and rs2241766 (T45G), may affect disease susceptibility. They have been associated with serum adiponectin (20)(21)(22)(23)(24)(25)(26), obesity (21,25,27,28), insulin sensitivity (18,21,29), type II diabetes (17,20,30) and coronary artery disease (24,31). However, some of these associations have been unable to be confirmed in other studies and the results have been controversial (32)(33)(34).…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, they observed that adiponectin serum concentration inversely correlated with tumor size and cancer stage. Fukumoto et al observed in patients with adenoma a slightly lower adiponectin serum concentration than in healthy controls (17). Kumor et al observed in patients with colorectal adenomas and carcinoma lower serum adiponectin concentrations than in the control group (18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, some studies showed lack of any association between ApN plasma levels and the development of colorectal cancer and an inverse relationship with ApN levels was reported only for large adenomas (≥5 mm) (Lukanova et al, 2006;Fukumoto et al, 2008). Yamauchi et al demonstrated that ApN acts via its two receptors, namely Adiponectin receptor-1 (Adipo-R1) and Adiponectin receptor-2 (Adipo-R2) (Yamauchi et al, 2003).…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Later in his prospective case control study, Wei EK et al suggested that the risk of colorectal cancer is higher in patients with low adiponectin plasma levels (Wei et al,2005). Conversely Fukumoto J et al revealed that there is no measurable association between circulating levels of adiponectin and colorectal adenomas (Fukumoto et al,2008). The mechanisms of these effects are also a mystery.…”
Section: Discussionmentioning
confidence: 99%